Does responsibility accounting in public universities matter? - Philip Owino (Taylor & Francis Group, 2016)
Responsibility accounting is an administrative accounting method that measures the results of each responsibility centre. The concept of responsibility accounting is vested in costs and revenues performance. Managers are evaluated based on what is under their control. Hence, the purpose of this paper is to examine if responsibility accounting matters in Ugandan public universities. The paper adopted a cross-sectional survey that included both quantitative and qualitative approaches to find out if responsibility accounting matters. The qualitative data supplement quantitative data. The findings indicate that there is a system of responsibility accounting. Costs and revenues are managed at respective departments. Heads of department have authority to manage their budget-allocated estimates. They are responsible for their decisions against their budgets or votes. Costs and/or revenues are accumulated and reported upward from departments and faculties to university authorities. This study signifies that responsibility accounting follows hierarchical patterns in public universities.